Real-world reduction in healthcare resource utilization following treatment of opioid use disorder with reSET-O, a novel prescription digital therapeutic. (2nd January 2021) - Velez, Fulton F.; Colman, Sam; Kauffman, Laura; Ruetsch, Charles; Anastassopoulos, Kathryn
ABSTRACT: Introduction: Buprenorphine medication assisted treatment (B-MAT) adherence for opioid use disorder (OUD) is suboptimal. reSET-O, an FDA-cleared prescription digital therapeutic, delivers neurobehavioral therapy (community-reinforcement approach+fluency training+contingency management) to B-MAT-treated OUD patients. Methods: This retrospective claims study (10/01/2018-10/31/2019) evaluated healthcare resource utilization up to 6 months before/after reSET-O initiation. Repeated-measures negative binomial models compared incidences of encounters/procedures. Net change in costs was assessed. Results: Among 351 patients (mean age 37; 59.5% female; 82.6% Medicaid), 334 had pharmacy claims and 240 (71.9%) received buprenorphine pre-/post-index (medication possession ratio 0.73 and 0.82, respectively; P =  0.004). Facility encounters decreased, with 45 fewer inpatient ( P =  0.024) and 27 fewer emergency department (ED) visits ( P =  0.247). Clinical encounters with largest changes were drug testing (638 fewer; P <  0.001), psychiatry (349 fewer; P =  0.036), case management (176 additional; P =  0.588), other pathology/laboratory (166 fewer; P =  0.039), office/other outpatient (154 fewer; P =  0.302), behavioral rehabilitation (111 additional; P =  0.124), alcohol/substance rehabilitation (96 fewer; P =  0.348), other rehabilitation (66 fewer; P =  0.387), mental health rehabilitation (61 additional; P =  0.097), and surgery (60 fewer; P =  0.070). Changes in facility/clinical encounters saved $2, 150/patient. Conclusion: reSET-O initiation was associated with fewer inpatient, ED, and other clinical encounters, increased case management/rehabilitative services, and lower net costs over six months. Expert Opinion: Real-world evidence is helpful in evaluating the effectiveness of interventions in usual-care conditions, outside of controlled research environments. Large observational studies based on health care claims are important to understand the actual pharmacoeconomic and outcomes impact of interventions at the health care system and population level.